Menguak Kebenaran Ayat Rada’ah Berdasar Fakta Empiris - Suwito, Suwito (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2015)
This article discusses about the relationship between the development of modern science and technology and so many recent studies on the content of the nutrients found in breast milk. Based on the experiment carried out in Canada, there is a number of artificial milk as sold in stores today. But scientists assert that the artificial milk is quite impossible to replace breast milk, because the two kinds of milk have a different content. Another experiment is on one hundred and fifty infants. They were divided into three groups: one group were breastfed for less than two years, the second group of breast-fed for two years, and the last group were breastfed for more than two years. The research proves that the ideal time for mothers to breastfeed their infant is two years. The children who got breast milk in less than two years they will biologically get some troubles. While, those who got breast milk in more than two years, there is accumulation of partial material or substance in the body cells that cannot be thrown out. If the above results are communicated to the verses of al-Qur'an, it can be concluded that al-Qur'an, which was revealed since fourteen centuries ago, is still in line with the modern science and technology. [Artikel ini membahas tentang hubungan antara perkembangan ilmu pengetahuan dan teknologi modern dan begitu banyak studi terbaru pada isi nutrisi yang ditemukan dalam ASI. Berdasarkan percobaan yang dilakukan di Kanada, ada sejumlah susu buatan sebagai dijual di toko-toko. Tetapi para ilmuwan menegaskan bahwa susu buatan sangat mustahil untuk menggantikan ASI, karena kedua jenis susu memiliki kandungan yang berbeda. Percobaan lain adalah pada seratus lima puluh bayi. Mereka dibagi menjadi tiga kelompok: satu kelompok disusui selama kurang dari dua tahun, kelompok kedua diberi ASI selama dua tahun, dan kelompok terakhir disusui selama lebih dari dua tahun. Hasil penelitian membuktikan bahwa waktu yang ideal bagi ibu untuk menyusui bayi mereka adalah dua tahun. Anak-anak yang mendapat ASI dalam waktu kurang dari dua tahun secara biologis akan mendapatkan beberapa masalah. Sementara, mereka yang mendapat ASI dalam lebih dari dua tahun, terjadi penumpukan bahan parsial atau zat dalam sel-sel tubuh yang tidak dapat dibuang. Jika hasil di atas dikomunikasikan kepada ayat-ayat al-Qur'an, maka dapat disimpulkan bahwa al-Qur'an, yang telah diturunkan sejak empat belas abad yang lalu, masih sejalan dengan ilmu pengetahuan modern dan teknologi.]